EFEKTIVITAS ROLE PLAY TERHADAP PENGETAHUAN KEAMANAN MAKANAN PADA ANAK USIA SEKOLAH - Lita Heni Kusumawardani; Aprilia Kartikasari; Koernia Nanda Pratama (Jurnal Ilmu Keperawatan Komunitas, 2020)
Health problems due to unsafe food in Indonesia often occur, especially among school-aged children. Currently, the phenomenon of food poisoning in Indonesia is quite concerning. School aged children who are given health education related to food safety to prevent the incidence of food poisoning. This study aimed to see the effect of playing a role in improving knowledge of food safety in elementary school children in Purwokerto City, Banyumas Regency. The research method used a quasi experimental design pre-post test using a control group. The number of research samples was 40 school age children aged 6-12 years. Groups were given treatment in the form of groups as the implementation of role play for 4 weeks 4 times. Analysis of data used t- impaired test and pooled t-test. The results of this study were a health education method with role playing which was able to improve knowledge of food safety in school children significantly p <0.05. In conclusion, the role play method can be used to improve knowledge of food safety in school age children. The role play method is expected to be used as an effective and interactive educational intervention for elementary school aged children.